Multiple amyloid lesions in the lateral pharyngeal wall: a case report - Claros, Andres; Blebea, Cristina; Clarós, Pedro (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Amyloidosis represents a diverse group of disorders that have in common the deposition of amyloid protein in various extracellular tissues. Its clinical presentation may be systemic or localised. However, regions in the head and neck are rarely affected. This report discusses the case of a 57 year old man with a history of 6 years of left ear non-pulsatile tinnitus, who at the physical examination presented a polilobulated, yellowish oropharyngeal lesion, behind the left posterior pillar of the tonsil. Biopsy of the lesion sustained the diagnostic of light chain amyloidosis and subsequent evaluation was significant for establishing the diagnosis of localised amyloidosis. While further investigations a second laryngeal lesion was encountered. We present a case report of double synchronous amyloidosis localization on head and neck and asymptomatic lesions and discuss the implications for diagnosis and treatment.